The relationship between binge-watching and psychological well-being among Indonesian university students - Shabrina, Nasywa Nabila Nur; Palupi, Listyati Setyo (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to investigate the relationship between binge-watching and psychological well-being among university students, a population particularly susceptible to fluctuations in mental health due to academic, personal, and social pressures. A quantitative, survey-based design was employed. The sample consisted of 161 university students aged 18-25 years who had engaged in binge-watching, defined as viewing a minimum of three consecutive episodes of a television series within a single sitting. Psychological well-being was measured using the Short-form Ryff’s Psychological Well-being Scale Ryff & Keyes (1995)while binge-watching tendencies were assessed through the Binge-watching Addiction Questionnaire (Forte et al., 2021). Data analysis was conducted via Pearson’s product-moment correlation using IBM SPSS Statistics version 26 for MacOS. Results demonstrated a statistically significant, albeit modest, positive correlation between binge-watching frequency and psychological well-being, suggesting that increased engagement in binge-watching may coincide with heightened perceptions of psychological flourishing among students, whereas lower levels of engagement may be linked to diminished psychological well-being.